Arboviruses in the Teaching of Natural Sciences: an analysis of the textbook of public high schools (Research, Society and Development, 2022)
The use of textbooks in the Teaching of Natural Sciences is a resource of great relevance, in view of the abstraction of many concepts and scientific phenomena. However, teaching based on the presentation of technical terms and description of phenomena often discourages students in their processes of learning. Arboviruses, viral infections transmitted by viruses, are public health problems in Brazil, being the object of knowledge in curricular matrices. Thus, this work aims to analyze the teaching of arboviruses in the light of the textbook, in public high schools. For this research, the analysis of two textbooks approved in the PNLD 2016-2019, used in the Ceará cities of Acopiara and Jucás, was carried out. The research with a qualitative approach was developed on two main fronts: analysis of the textbook and analysis of the teachers' pedagogical practices. The approach to the theme “arboviruses” was developed based on three main axes: theoretical content, visual resources and complementary resources. Twelve teachers, who work in five public schools, as High School Biology teachers, participated in the research. The analysis of the books showed that there is a divergence in the way the content of arboviruses is approached, although both books lack illustrations, greater detailing of infections, preventive measures with a focus on health education and scientific research, with scientific literacy being one of the analysis points of this study. In pedagogical practice, it is common for teachers to seek to complement the deficiencies found in textbooks. In general, books, very focused on content, end up not being connected to the reality of the students, requiring the teacher to look for such association in other sources.